Paraspinal Lumbar Spine Approach - Wiltse Access - Rabelo, Nícollas Nunes; Silva, Bruno Nascimento Bettencourt da; Silveira Filho, Luciano José; Passos, George Santos dos; Pereira, Vitor Hugo Honorato; Dias Junior, Luiz Antônio Araujo; Dias, Luiz Antônio Araujo; Tanaka, Koji (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Introduction Technical developments in spinal surgery have reduced the number of surgical incisions and of the length of time for the procedure.Objective Describe topographical landmarks, anatomy and characteristics of the Wiltse access, a paraspinal approach to the lumbar spine.Methods A review of the literature was performed using as databases: PubMed, Embase, Science Direct, the Cochran Database and Google Scholar. Total 22 papers met the inclusion criteria, and they were all published between 1959 and 2016.Discussion The Wiltse approach is performed by median skin incision with lateral muscle dissection between the multifidus and the longissimus muscles, in a natural pathway. This approach allows access to the pedicles and to the lateral recess, enabling the performance of posterior spinal fusion and decompression and minimally invasive discectomy techniques. This access is less traumatic than the median approach, and it is ideal for lower levels, like L4–5 and L5-S1.Conclusion The authors strongly encourage this approach because they believe that, when well-indicated, the benefits outweigh the disadvantages and complications due to the fact that it is a less invasive procedure.
Keywords: Wiltse access; lumbar spine; paraspinal approach; spine surgery